W is for wasted ebook - Grafton, Sue (Kinsey Millhone, 2013)
Private investigator Kinsey Millhone finds shocking connections between two seemingly unrelated deaths in this #1 New York Times bestselling mystery in the Alphabet series. The first victim is a local PI of suspect reputation, gunned down near the beach at Santa Teresa. The second is a John Doe found on the beach six weeks later with a slip of paper with private detective Kinsey Millhone’s name and number in his pocket. Two seemingly unrelated deaths: one man murdered, the other apparently dead of natural causes. But as Kinsey digs deeper into the mystery of the John Doe, some very strange links begin to emerge. Not just between the two victims, but also to Kinsey’s past. And before long Kinsey, through no fault of her own, is thoroughly compromised...